Обобщение схем для определения параметра учета влияния расстояния от точки физического поля до точечного источника энергии - Мостовенко, Александр Владимирович (КНУБА, 2020)
В данной работе представлено обобщение двух схем для определения параметра учёта влияния расстояния от произвольной точки физического поля до точечного источника энергии. Ранее обе эти схемы основывались на центральном проецировании [1]. Первая схема позволяла учитывать неограниченное расстояние между точкой физического поля и точечным источником энергии. Аналитическое описание этой схемы представляет собой равностороннюю гиперболу, которую можно использовать вместо центрального проецирования для определения параметра t учёта влияния расстояния между указанными точками. Вторая схема упрощает определение параметра t за счёт ограничения расстояния l, влияющего на потенциал произвольной точки физического поля, условно считая, что существует такое максимальное расстояние lmax , при котором потенциал энергии в точке физического поля практически отсутствует. This paper presents a generalization of two schemes for determining the parameter for taking into account the influence of the distance from an arbitrary point of a physical field to a point source of energy. Previously, both of these schemes were based on central projection [1]. The first scheme made it possible to take into account the unlimited distance between the point of the physical field and the point source of energy. The analytical description of this scheme is an equilateral hyperbola, which can be used instead of central projection to determine the parameter t taking into account the influence of the distance between the indicated points. The second scheme simplifies the determination of the parameter t by limiting the distance l, which affects the potential of an arbitrary point of the physical field, conditionally assuming that there is a maximum distance lmax at which the energy potential at the point of the physical field is practically absent. In this study, two previously presented circuits were generalized to determine parameter t, which takes into account the influence of the distance from the physical field point to the point energy sources. These schemes were based on central projection, which in this study was replaced by matching the points of the two axes using a hyperbolic constraint.
Generalization of cicuits for determining the accounting parameter of the distance from tne physical field point to the point energy sources
Keywords: physical field, energy; point source of energy; distance; influence of distance; energy potential; hyperbolic dependence; parameter of influence of distance; физическое поле; энергия; точечный источник энергии; расстояние, влияние расстояния; потенциал энергии; гиперболическая зависимость; параметр влияния расстояния